1990
DOI: 10.1007/bf01311291
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 41 growth in semi-permissive cells shows multiple-hit kinetics

Abstract: Adenovirus type 41 infection of semi-permissive Chang conjunctival cells, monitored by fluorescent focus assay, followed multiple-hit kinetics. In non-permissive human cells, type 41 showed infectivity with two-hit kinetics in the presence of type 2. Type 41 infectivity was seen to be directly proportional to input concentration (one-hit) only in 293 cells, a continuous human line expressing Ad 5 E1 products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, Ad41 has been successfully propagated in several cell lines, including G293, a line of human embryo kidney cells transformed with the Ad5 E1 region (13,28). Ad41 is known to infect G293 cells in accordance with a single-hit model, which means that only one virus is sufficient to infect G293 cells productively (27). This single-hit model suggests that an mRNA RT-PCR assay should be able to detect a single infectious Ad41 particle in a G293 cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ad41 has been successfully propagated in several cell lines, including G293, a line of human embryo kidney cells transformed with the Ad5 E1 region (13,28). Ad41 is known to infect G293 cells in accordance with a single-hit model, which means that only one virus is sufficient to infect G293 cells productively (27). This single-hit model suggests that an mRNA RT-PCR assay should be able to detect a single infectious Ad41 particle in a G293 cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained in part by a reduced transactivation of other early promoters by Ela products and therefore longer periods of time required for accumulating critical concentrations of certain products. In keeping with this, it was found that four to five infectious virus particles are required to infect productively each Chang conjunctival cell (Tiemessen & Kidd, 1990). Collaboration between a number of genomes may therefore be necessary to attain critical levels of a certain product(s) to allow progression of the infectious cycle.…”
Section: Apparent Defectiveness (I) Introductionmentioning
confidence: 90%
“…Genes encoding a putative 59 kDa fibre polypeptide in Ad40 (Kidd & Erasmus, 1989) and 60.5 kDa fibre polypeptide in Ad41 (N. J. Pieniazek et al, 1989a;Kidd et al, 1990) have been characterized. There is a high degree of identity between the 59 kDa and 60.5 kDa fibre proteins of these viruses, except in the shaft region.…”
Section: Late Regionsmentioning
confidence: 99%
See 2 more Smart Citations